Urogenital and pelvic complications in the Ehlers-Danlos syndromes and associated hypermobility spectrum disorders: A scoping review - Gilliam, Elizabeth (Clin Genet, 2019)
The Ehlers-Danlos syndromes (EDS) and associated hypermobility spectrum disorders (HSD) are a heterogenous group of connective tissue disorders associated with significant morbidity. The urogenital aspects of these disorders are understudied and there is little guidance on the prevalence, types, or outcomes of urogenital complications in EDS/HSD. Our objective was to perform a scoping review to characterize and synthesize the literature reporting urogenital and pelvic complications in EDS/HSD patients. We performed a systematic search of three databases (Medline, CINAHL, Embase) to January 2019. English language, full-text articles reporting on urogenital or pelvic complications in EDS/HSD were included. A total of 105 studies were included (62 case reports/series, 43 observational) involving patients with hypermobile (23%), vascular (20%), classical (12%) EDS, and HSD (24%). Some studies looked at multiple subtypes (11%) or did not report subtype (33%). Reported complications included urinary (41%), gynecological (36%), obstetrical (25%), renal (9%), and men’s health problems (7%), with some studies reporting on multiple areas. Urinary and gynecological complications were most prevalent in patients with HSD, while a broad range of complications were reported in EDS. While further research is required, results suggest a higher index of suspicion for urogenital problems is probably warranted in this population.